The Linkages between Corporate Social Responsibility and Financial Performance: The Moderating Role of Ownership Structure - hamida; M. Arsyadi Ridha (LP2M IAIN Palopo, 2026)
This study aims to analyze the relationship between corporate social responsibility and financial performance with the moderating role of ownership structure for manufacturing companies in the consumer goods sector. This study used 46 samples of manufacturing companies in the consumer goods sector listed on the Indonesia Stock Exchange for the period 2017-2022 and the data collection technique used was purposive sampling. This study uses panel data regression analysis and MRA (Moderated Regression Analysis). The results showed that CSR significantly has a positive effect on ROA. While foreign ownership, managerial ownership and institutional ownership are not able to moderate the relationship between CSR and financial performance.